2016
DOI: 10.2507/26th.daaam.proceedings.067
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of friction parameters in the process of wood welding without additional adhesives

Abstract: Wood welding technologies have been developed as a new way of timber bonding without any adhesives. Welding of wood is a process where chemical and physical reactions take place. During the process of welding, the surface layers of wood (lignin) melt, due to high pressure and temperature, which is usually generated by mechanical friction of the elements being in contact. Friction can be induced by vibration or by rotation. This paper presents the results of our own research of the influence of the injection di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Rotary welding with wooden dowels has been successfully introduced for both softwoods (fir, pine, spruce) and hardwoods (beech, birch, fir, larch, maple, oak), and also for bamboo [47][48][49][50][51][52][53][54]. Due to differences in the anatomical structures and chemical compositions of the main wood components (particularly hemicelluloses and lignin), the welding performances of different species are highly variable [48].…”
Section: Rotary Welding Of Wooden Dowelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotary welding with wooden dowels has been successfully introduced for both softwoods (fir, pine, spruce) and hardwoods (beech, birch, fir, larch, maple, oak), and also for bamboo [47][48][49][50][51][52][53][54]. Due to differences in the anatomical structures and chemical compositions of the main wood components (particularly hemicelluloses and lignin), the welding performances of different species are highly variable [48].…”
Section: Rotary Welding Of Wooden Dowelsmentioning
confidence: 99%
“…There is a risk that the progressive reduction in diameter of the dowel reduces the welding quality in the deeper welding area. It has been reported that the lowest welding temperature along the pre-drilled hole was detected at the bottom of the hole due to the wear of the tip of the dowel [49,60,62].This problem can be remedied by making the hole with two different diameters at different depths [49,52,60,63].…”
Section: Rotary Welding Of Wooden Dowelsmentioning
confidence: 99%
“…During this process, the lignin of the wood surfaces melts due to the heat generated. Once the vibration stops, the melted lignin solidifies, bonding the two pieces of wood together (Gfeller et al 2003;Horman et al 2016). The temperature of the welding surface should be in between lignin's melting temperature and its thermal decomposition temperature (170 C to 280 C).…”
Section: General Principles Of Wood Weldingmentioning
confidence: 99%
“…1. Methods of wood welding where PZ is welding pressure, VZ is welding time, FR is friction force, and a is amplitude of vibratory movement (Horman et al 2016) The same mechanism takes place when a rotating wood dowel is inserted into a pre-drilled hole on a wood piece, as shown in Fig. 2.…”
Section: General Principles Of Wood Weldingmentioning
confidence: 99%
“…Researchers have studied the performance enhancement aspects of single dowel rotary friction welding joints. Four methods, such as setting cross slots at the end of round wooden tenons, pre-drilled holes of wooden components with large outer and small inner fits, impregnation of round wooden tenons with ethylene glycol solution, and friction welding under 100 °C thermal conditions failed to improve the performance of the joint joints (Horman et al 2016). However, the use of smaller diameter wood components predrilled and rotary friction welded dry wood round tenons at room temperature can improve the performance of welded joints (Auchet et al 2010).…”
Section: Introductionmentioning
confidence: 99%